Improvement of thermoelectric performance of α‐In2Se3 upon S incorporation. Issue 4 (24th November 2015) - Song, Zhiliang; Liu, Haiyun; Du, Zhengliang; Liu, Xianglian; Cui, Jiaolin
Abstract : In this work, we have observed the enhancement of carrier concentration in α‐In2 Se3 at a specific S content. This enhancement results from avoiding the annihilation of defects, such as VIn and interstitial Ini acting as donors, via the rearrangement of both the cationic and anionic disorders. Therefore, there is a remarkable improvement in electrical conductivity ( σ ). For example, the sample α‐In2 S0.05 Se2.95 perpendicular to the pressing direction ( C ┴ ) gives the highest σ value of 5.56 × 10 3  Ω −1  m −1 at 923 K, while the virgin α‐In2 Se3 gives only 9.17 × 10 2  Ω −1  m −1 . In addition, there are dual effects on the lattice thermal conductivity ( κ L ) resulting from the stabilization of the lattice structure caused by the rearrangement of defect disorder and the lattice distortion from the formation of defect SSe . Therefore, the lattice contribution ( κ L ) in S‐incorporated α‐In2 Se3 remains relatively high at high temperatures. As a consequence, we have improved the thermoelectric performance, achieving a ZT value of 0.67 for α‐In2 S0.05 Se2.95 at 923 K, which is about 2.8 times that of virgin α‐In2 Se3 ( ZT  = 0.24 at C ┴ ).